Research on large-scale identity authentication architecture based on combined symmetric key - LIU Tong; XU Guan-ning (Tongxin xuebao)
A large-scale real-name authentication architecture and key management protocol based on combined symmet-ric key algorithm were proposed.With the CSK algorithm and smart card technology, the authentication process can be finished in the chips, and the management of large-scale keys can be simplified to the management of small-scale key seeds.The security of the proposed architecture is analyzed and the experimental results are shown.It is obvious that the abilities of large-scale identity authentication and management are improved while the building cost is reduced evidently with the application of the proposed architecture.It is an applicable solution for real-name authentication network.